Rhetorical strategies in late antique literature : images, metatexts and interpretation - Quiroga Puertas, Alberto J., 1978- (Mnemosyne, bibliotheca classica Batava. Supplementum ;, 2017)
Rhetorical Strategies in Late Antique Literature: Images, Metatexts and Interpretation is a collection of essays that survey the rhetorical tropes and the metaliterary dimension of works by important authors in a period marked by intense and thriving contact between Classical paideia and Christian culture. The contributions of this volume dissect the reuse of Classical literature and the deployment of rhetorical techniques in the creation of texts and images meant for use in cultural and religious debates by building on recent interpretations of the late antique cultural landscape as a milieu in which our understanding of religious dichotomies requires a more nuanced reassessment. The authors treated in this volume include Eusebius of Caesarea, Methodius of Olympus, Gregory of Nazianzus, Nonnus and the emperor Julian.